-6x-7-5x=-73

Simple and best practice solution for -6x-7-5x=-73 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6x-7-5x=-73 equation:


Simplifying
-6x + -7 + -5x = -73

Reorder the terms:
-7 + -6x + -5x = -73

Combine like terms: -6x + -5x = -11x
-7 + -11x = -73

Solving
-7 + -11x = -73

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + 7 + -11x = -73 + 7

Combine like terms: -7 + 7 = 0
0 + -11x = -73 + 7
-11x = -73 + 7

Combine like terms: -73 + 7 = -66
-11x = -66

Divide each side by '-11'.
x = 6

Simplifying
x = 6

See similar equations:

| s^2-16s+80=0 | | 2x(3x+1)-6x^2=4 | | 4a+3(a+2)=2(3a+2) | | 7-3(x)=12 | | 8+p=25 | | .05+25=3.00 | | [8w+8]=21 | | 41/5/3/5 | | 3(x+4)=x/2-8 | | -5x=-6-y | | 3y+y=12-5 | | 2=15-q | | (X/7)-6=36 | | 1-7b=-8(1+2b) | | -5/6q-(q-1)=1/4(-9+80) | | (3x-7)=(9x-5) | | 1/2x-3=5/8x | | 7(x+3)-1=5(x+4)+10 | | 5x^2+2x-192=0 | | 2t-6=9 | | 10+y=13 | | -12x+4y=-20 | | x-5=2(4x-3) | | 2.5/10=x/12 | | -13=5(1+4m)-3 | | 13-12x=2y | | -123+12x=x+108 | | .7x-.6(60+x)=-.5(60) | | 25+10(12-x)=2x-7 | | 8=18-2g | | 4(1+2x)=7(x-5) | | -21=7x |

Equations solver categories